Mechanical Behavior of Red Sandstone under Incremental Uniaxial Cyclical Compressive and Tensile Loading. (31st December 2017) - Zhao, Baoyun; Liu, Dongyan; Huang, Tianzhu; Huang, Wei; Liu, Wei
Abstract : Uniaxial experiments were carried out on red sandstone specimens to investigate their short-term and creep mechanical behavior under incremental cyclic compressive and tensile loading. First, based on the results of short-term uniaxial incremental cyclic compressive and tensile loading experiments, deformation characteristics and energy dissipation were analyzed. The results show that the stress-strain curve of red sandstone has an obvious memory effect in the compressive and tensile loading stages. The strains at peak stresses and residual strains increase with the cycle number. Energy dissipation, defined as the area of the hysteresis loop in the stress-strain curves, increases nearly in a power function with the cycle number. Creep test of the red sandstone was also conducted. Results show that the creep curve under each compressive or tensile stress level can be divided into decay and steady stages, which cannot be described by the conventional Burgers model. Therefore, an improved Burgers creep model of rock material is constructed through viscoplastic mechanics, which agrees very well with the experimental results and can describe the creep behavior of red sandstone better than the Burgers creep model.